Peningkatan Kemampuan Menulis Puisi Melalui Teknik Pembelajaran Kolaboratif - Novia, Lisa (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to improve the skills of writing poetry class XII student of SMK Prima Unggul AK through collaborative engineering. This type of research is the Classroom Action Research (PTK). Subjects in this study were students of class XII SMK Prima Unggul AK ciledug academic year 2015/2016 totaling 40 students. This action research was conducted in two cycles each cycle there are four components, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). Data collection techniques such as observation, interviews, questionnaires, tests, field notes, documents student assignments, and documentation of the learning activities. Data were analyzed using descriptive analysis techniques of qualitative and quantitative. Qualitative data analysis is used for the qualitative data such as the results of field observations, field notes and interviews. Analysis of quantitative data used for quantitative data obtained from the test writing poetry before and after given action. The results of this study indicate that the application of engineering collaboration can improve the skills of writing poetry class XII student of SMK Prima Unggul AK ciledug. Process improvement can be seen in the implementation of the learning process that lasted more efficient and conditions of pupils more active role in learning to write poetry because activity is a fun activity.